Nutrition economics: Four analyses supporting the case for whole grain consumption. (May 2022) - Miller, Kevin B.; Grafenauer, Sara J.; Martikainen, Janne
Highlights: Models from four studies provide significant healthcare cost savings for increased whole grain. Range in healthcare cost savings from USD$4516 - $10, 624/person represents 9.04%–16.89% of GDP. Required increase in whole grain intake as little as a slice of bread or a bowl of breakfast cereal. Countries do not prioritise whole grains within dietary guidelines or front-of-pack labelling.